THE EFFECT OF PROMOTION AND HEDONIC SHOPPING MOTIVATION ON COSTUMER IMPULSE BUYING ON ZALORA ONLINE SHOPPING SITES - Ismi Ariani; Gugyh Susandy; Devy Widya Apriandi (JABI (Journal of Accounting and Business Issues), 2019)
The purpose of this study is to determine the effect of Hedonic Promotion And Shopping Motives Against Impulse Buying On Zalora Online Shopping Site. Method of research used is explanatory survey method. The sample selection was done by using purposive sampling technique with the number of samples of 100 respondents. The data used is interval data. Statistical methods for data testing using the SPSS 20 for Windows program. By using multiple linear regression analysis, the results of research show that Promotion has significant effect to Impulse Buying with t count value > t table and Hedonic Shopping Motives have significant effect to Impulse Buying with value t count > t table. Likewise with the Promotion and Hedonic Shopping Motives simultaneously significant effect on Impulse Buying with the value of F count > F table.